Enhancement of rectangular shape antenna with electromagnetic band gap (EBG) at 6GHz / Mohammad Noor Sazali - Sazali, Mohammad Noor (2013)
This thesis presents the design, analysis, simulation, fabrication and measurement of Rectangular Shape Antenna using Metamaterial Structures with Electromagnetic Band Gap (EBG) and also investigates the potential properties of the proposed antenna use in C-band application. The proposed and the conventional rectangular patch antenna are designed at a center of operating frequency of 6 Ghz to meet the WLAN applications. The antenna design was simulated by using Rogers RO3003 as the substrate of the antenna. All the simulation work for both patch antennas was design by using Computer Simulation Technology (CST) Microwave Environment Studio. Metamaterial characteristic which is exhibit negative permittivity and permeability of the proposed EBG structures have been verified using Nicolson Ross Weir (NR W) method. The performance of the potential properties for both antennas was then compared in term of directivity, gain, return loss, bandwidth and the size of patch antenna. As a result of combining the rectangular patch with EBG structure, the potential properties of the proposed antenna increase such as return loss (S 11 ), Voltage Standing Wave Ratio (VSWR) and size of the antenna patch reduces to a great extent in comparison to the rectangular patch without EBG. The return loss (S 11) for both antennas meet the specification of -10 dB cut off.